Pengembangan Instrumen Asesmen Kinerja untuk Menilai Keterampilan Proses Sains Peserta Didik pada Praktikum Saponifikasi - Aztiannisa Zahra; Nahadi; Wiwi Siswaningsih (Postgraduate, University of Mataram, 2025)
This study aims to develop a performance-based assessment instrument to assess students’ Science Process Skills (SPS) for saponification laboratory activities. This research is an instrument development study, consisting of four main stages: planning, development, validation, and pilot testing. A total of twelve 11th grade students from a high school in Bandung participated in pilot testing phase to evaluate the instrument’s reliability. This performance-based instrument covers 27 performance aspects aligned with six SPS indicators: predicting, planning, implementing, observing, communicating, and interpreting. This instrument demonstrates strong content validity, with a CVI of 0.99. Inter-rater reliability was analyzed using Kendall’s W Coefficient. The results show variable agreement results: 2 aspects showed very strong agreement, 3 aspects showed strong agreement, and 11 aspects showed weak agreement. These findings suggest the need to refine several instrument items to enhance inter-rater reliability. The practicality of the instrumen, evaluated through assessors, resulted in a score of 3.35 on a scale of 4.00, indicating the instruments is very practical for further implementation. Overall, the final product of instrument is valid and practical for assessing students’ SPS in the saponification lab activities, though further improvements are necessary to improve inter-rater agreement.